2021
DOI: 10.1530/joe-21-0040
|View full text |Cite
|
Sign up to set email alerts
|

DHT causes liver steatosis via transcriptional regulation of SCAP in normal weight female mice

Abstract: Hyperandrogenemia (HA) is a hallmark of polycystic ovary syndrome (PCOS) and is an integral element of nonalcoholic fatty liver disease (NALFD) in females. Administering low dose dihydrotestosterone (DHT) induced a normal weight PCOS-like female mouse model displaying NAFLD. The molecular mechanism of HA-induced NAFLD has not been fully determined. We hypothesized that DHT would regulate hepatic lipid metabolism via increased SREBP1 expression leading to NAFLD. We extracted liver from control and low dose DHT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…The sex-specificity of this hormone was identified in this process. In this regard, although beneficial in males, excessive androgen impaired hepatic lipid metabolism and promoted hepatic steatosis in androgen-treated female rodents, as showed by Seidu et al in 2021 [139], which was similar to the results obtained in PCOS females (Figure 2).…”
Section: Role Of Other Hormones In Fueling Ir: a Matter Of Sex?supporting
confidence: 88%
“…The sex-specificity of this hormone was identified in this process. In this regard, although beneficial in males, excessive androgen impaired hepatic lipid metabolism and promoted hepatic steatosis in androgen-treated female rodents, as showed by Seidu et al in 2021 [139], which was similar to the results obtained in PCOS females (Figure 2).…”
Section: Role Of Other Hormones In Fueling Ir: a Matter Of Sex?supporting
confidence: 88%
“…Androgen signaling and hepatic lipid metabolism. Many studies have shown that altered androgen levels impair lipid metabolism and cause hepatic steatosis in both humans and rodents [ 140 , 171 , 186 , 187 , 188 , 189 ], pointing to a role of androgen signaling in the regulation of lipid metabolism in the liver.…”
Section: Androgen Signaling In the Healthy Livermentioning
confidence: 99%
“…Although beneficial in males, androgen excess impairs hepatic lipid metabolism and promotes hepatic steatosis in androgen-treated female rodents [ 189 , 191 ], resembling what observed in PCOS women [ 169 ]. In female mice, DHT increases SCAP (sterol regulatory element-binding protein cleavage-activating protein) protein expression and SCAP-SREBP1 binding, thus favoring the nuclear localization of SREBP1 and promoting DNL [ 189 ].…”
Section: Androgen Signaling In the Healthy Livermentioning
confidence: 99%
See 1 more Smart Citation
“…A low-dose dihydrotestosterone (DHT)-induced model of normal weight PCOS-like female mice with NAFLD showed that DHT enhanced the binding of an androgen receptor (AR) to an androgen response element (ARE) in sterol regulatory element-binding protein (SREBP) cleavage activating protein (SCAP) intron 8, elevating the SCAP-SREBP1 interaction, leading to an increase in nuclear SREBP1, and resulting in increased hepatic adipose de novo synthesis. 42 According to the literature, PCOS-like rats with 12 weeks of induced DHT exposure showed that chronic androgen overload leads to insulin resistance and hepatic steatosis by affecting mitochondrial function and causing apoptosis and autophagy imbalance. 43 In letrozole-induced PCOS-like rat models and DHT-treated HepG2 models, excess androgens cause steatosis by inhibiting the adenosine monophosphate (AMP)-activated protein kinase alpha pathway.…”
Section: Risk Factors For Nafld In Pcosmentioning
confidence: 99%